Is Care Compatible with The Tyranny of Immediacy? on substituting rhythm for cadence - Christine Leroy (Journal of Philosophical Investigations)
The article specifies the human being based on the respiratory cycle, referring to the etymology of the word “spirit”. This word shares its root with the French word respiration (“breathing”) as well as the verb “to inspire,” suggesting breath and animation. Human temporality is made up of organic rhythmicity, from a weighing body that experiences itself as inscribed in time – this is the authentic meaning of the word “to exist”: to come from nowhere, without time, to somewhere, at some time. This article questions the compatibility between the demand for temporal efficiency, characteristic of the modern industrial age and the technophile ideology of communication, and the “service society” which purports to be more “caring” than the industrial one. Highlighting the suppression of the passage of time characteristic of the ideology of communication, where “time” is frozen in a self-reproducing present with no past or future, the author asserts that humane care is radically incompatible with a society that subsumes humanity, inscribed in time and in need of breath, under the ideology of a perpetual present. It is precisely on the basis of what specifies the human, namely breathing and desire, that the author proposes to consider how care might be possible in an ultra-technologized world. Drawing on an imaginary of movement and inspiration/aspiration/breathing deployed in choreographic performances and practices, the author invites the reader, as Simone Weil did, to substitute rhythm for cadence, to insert slowness into speed, and to favor the flow of time in a human reality that has become unbearable by dint of “modernization”. In so doing, we must reconsider head-on the fate that binds us, namely death, which no stasis in a perpetual present can eliminate, and which the metaphor of a risk of social necrosis invites us to reconsider. Accepting the passage of time, giving death back its face, is costly; but it's at this price that time can regain its humanizing value, as a sine qua non component of care.